Inequity in physician visits: the case of the unregulated fee market in Australia. (June 2020) - Pulok, Mohammad Habibullah; van Gool, Kees; Hall, Jane
Abstract: Equity is one of the key goals of universal healthcare coverage (UHC). Achieving this goal does not just depend on the presence of UHC, but also on its design and organisation. In Australia, out-of-hospital medical services are provided by private physicians in a market where fees are unregulated. This makes an interesting case to study equity. Using data from the Australian National Health Survey of 2014–15, we distinguish between the probability of any visit and the number of visits conditional on having any visit to analyse income-related inequity in general practitioner (GP) and specialist visits. We apply the horizontal inequity approach to measure the extent of inequity, and the decomposition method to explain the factors accounting for inequity. Our results show a small pro-rich inequity in the probability of any GP visit, but the distribution of conditional GP visits was concentrated among the poor. Inequity in the probability of any specialist visit was pro-rich. However, there was almost no inequity in conditional specialist visits. We find holding a concession card explained pro-poor inequity while income, education, and private health insurance contributed to pro-rich inequity in specialist visits. Although Australia has a universal health insurance system, there is unequal use (adjusted for health need) of physician services by socioeconomic status. This has implications for insurance design in other countries. Highlights: We find pro-rich inequity in the probability of GP and specialist visits in Australia. Conditional GP visits was pro-poor, but no inequity in conditional specialist visits. Contribution of concession card to inequity in physician visits was pro-poor. Income, education, and private health insurance contributed to pro-rich inequity. Our results has implications for insurance design in other developed countries.